Adaptation and validation of the portuguese version of the healthy life styles questionnaire - Batista, Marco (2018)
The aim of this study was the adaptation and validation of Healthy Lifestyle Questionnaire (EVS), of Jimenez Castuera (2004) adapted of Wold (1995), using an exploratory and confirmatory factor analysis of the measurement model, with a sample of sports veterans. In the exploratory and confirmatory factor analysis part 684 Portuguese veteran athletes of both genders, aged between 30 and 90 years (M=43.78 SD=8.61), of which 547 male subjects and 137 subjects were female, which are competitors of various sports. The main results showed that the psychometric qualities of both the exploratory factor analysis, and confirmatory factor analysis, proved the adequacy of adaptation performed, demonstrating that the factor structure (Adaptation to Sports Questionnaire EVS: 3 factors/20 items) It has quite acceptable levels of validity (?2 = 172.117, df=41, p = .000, ?2/g.l. = 4.190, CFI = .966, IFI = .966, MFI = .909, GFI = .955, AGFI = .927, RMR = .049, SRMR = .043, RMSEA = .068), with reasonable levels of internal consistency of the three primary factors (eating habits =.80; tobacco consumption =.91; resting habits =.84). This led us to conclude that the adaptation to the Sports of the Portuguese version of the EVS can be used with high confidence in the assessment of healthy lifestyles in the sports context.